Growth Dynamics of Flexor Muscle Fibers in Developing Male White Leghorn Chicks - Mayalata Dimpal; Rahul Kundu (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The study examines the relationship between fiber orientation, functional activity, and growth dynamics in the flexor muscle of a male white Leghorn chick. It tests three hypotheses: similar histochemical fiber typing in muscle mass, distribution patterns influenced by species' functional activities, and fiber growth dynamics related to somatic growth rate. The study confirmed the hypothesis that all three basic fiber types (red, pink, and white) grow exclusively through hypertrophy. True hyperplasia was not evident in any age group, possibly in the late embryonic stage. Some cases of pink and white fibers showed splitting into smaller ones. All three basic fiber types grew by hypertrophy, regardless of location or functional activity. Muscle fiber growth in this muscle mass was directly related to the chick's somatic growth rate.
Keywords: Muscle fibers; Growth dynamics; Chick; Flexor; Hypertrophy; Hyperplasia